Immunoglobulin G Subclass Response to a Meningococcal Quadrivalent Polysaccharide-Diphtheria Toxoid Conjugate Vaccine - Findlow, Helen (American Society for Microbiology, 2006)
Changes in the immunoglobulin G1 (IgG1)/IgG2 ratio following vaccination can indicate the activation of cellular control mechanisms typical of a T-cell-dependent response. We examined IgG subclass ratios in 17 healthy adults (26 to 55 years of age) before and 4 to 6 weeks following immunization with a quadrivalent meningococcal-polysaccharide diphtheria toxoid conjugate vaccine against serogroups A, C, Y, and W135. Serologic responses were determined by serum bactericidal antibody assay and serogroup-specific IgG, IgG1, and IgG2 enzyme-linked immunosorbent assay. Prevaccination serogroup A-specific IgG1/IgG2 ratios were <1 for all subjects and differed by subject for C, Y, and W-135. Postvaccination, significant increases in IgG, IgG1, and IgG2, were observed for all serogroups. Serogroup-specific IgG1/IgG2 ratios increased for group A (14/17 subjects, 88%), decreased in more than half of subjects for groups C (9/17, 53%) and W135 (12/17, 71%) and decreased for serogroup Y (16/17, 94%). IgG1/IgG2 ratios differed between individual vaccinees and were similar to the responses of adults who received pneumococcal conjugate vaccines or a monovalent C conjugate vaccine. Further studies on IgG subclasses following meningococcal polysaccharide and conjugate vaccination are needed.